2014
DOI: 10.1097/acm.0000000000000330
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Education Programs in Africa

Abstract: Although the CBE programs have similar goals, their strategies for achieving these goals vary. To identify approaches that successfully address the challenges, particularly with increasing enrollment, medical schools need to develop structured models and tools for evaluating the processes, outcomes, and impacts of CBE programs. Such efforts should be accompanied by training faculty and embracing technology, improving curricula, and using global/regional networking opportunities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 13 publications
0
35
0
Order By: Relevance
“…Given this commitment to sustained mentorship and supervision, MEPI, the HRH Program, and GHSP have all established “teaching” hospitals, health centers, and communities where trainees can witness firsthand how high-quality health care is delivered and good governance pursued across all levels of the health system [15,24,34]. To increase retention after graduation, the curricula and training materials developed through MEPI in 12 sub-Saharan African countries are specifically designed to prepare trainees for practice in remote and under-resourced health facilities [34,35].…”
Section: New Models For Increasing Health Workforce Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Given this commitment to sustained mentorship and supervision, MEPI, the HRH Program, and GHSP have all established “teaching” hospitals, health centers, and communities where trainees can witness firsthand how high-quality health care is delivered and good governance pursued across all levels of the health system [15,24,34]. To increase retention after graduation, the curricula and training materials developed through MEPI in 12 sub-Saharan African countries are specifically designed to prepare trainees for practice in remote and under-resourced health facilities [34,35].…”
Section: New Models For Increasing Health Workforce Capacitymentioning
confidence: 99%
“…To increase retention after graduation, the curricula and training materials developed through MEPI in 12 sub-Saharan African countries are specifically designed to prepare trainees for practice in remote and under-resourced health facilities [34,35]. Similarly, the GHSP has prioritized the acquisition of competencies and skills by physicians and nurses in rural areas [21].…”
Section: New Models For Increasing Health Workforce Capacitymentioning
confidence: 99%
“…One strategy used to mitigate this strain is to decentralize clinical training, or send medical students to non-tertiary-care settings for clinical rotations. 3,4 …”
mentioning
confidence: 99%
“…[14] This finding contradicts previous findings that the exposure to CBE in medical curricula increases the likelihood of graduates choosing to work in rural and under-served areas. [1,15] Perhaps it is not just exposure to CBE (which in practice spans each year at UZCHS), but the quality and nature of that exposure which impacts positively on graduate choice. Studies have shown that three main factors influence choice of rural practice by medical graduates, i.e.…”
Section: Common Challenges Shared With Other Mepi Schoolsmentioning
confidence: 99%
“…[1] Other key areas needing attention relate to the CBE curriculum, appropriate course materials, textbook availability and alignment with the central curriculum. These challenges may undermine a major aim of CBE, which seeks to expose students to rural and under-served communities with the objective of encouraging future practice in these areas.…”
Section: Common Challenges Shared With Other Mepi Schoolsmentioning
confidence: 99%